Policy, finance and technology in livestock development in sub-Saharan Africa: Some critical issues - Anteneh, A.; Anteneh, B. (1988)
Examines the role and importance of the livestock subsector of Africas' agricultural sector, its performance over the last two decades, the constraints which limit its development and the progress being made in solving theese constraints.